Scratch circle from the Passaic Formation (Late Triassic), West-Central New Jersey. Issue 4 (2nd October 2021) - Metz, Robert
ABSTRACT: Scratching, forming one sharply-defined, somewhat elliptical scratch circle, surrounds a narrow-filled tube probably formed by a plant stem. Water currents carrying sediment onto a lacustrine shoreline swirled around a plant leaf, etching out a partial scratch circle. Later settling of the finest material resulted in a veneer of mud filling the scratch circle.